Rancang Bangun Sistem Monitoring Data Sebaran Covid-19 Secara Real-Time menggunakan Arduino Berbasis Internet of Things (IoT) - Agus Herlan; Iskandar Fitri; Rini Nuraini (KITA Institute, 2021)
Covid-19 is a new type of disease caused by a virus from the coronavirus class. Covid-19 spreads between humans very quickly and spreads to several countries including Indonesia, in just a few months. In this digital era, the role of media including IoT technology itself is very important for the development of information distribution in a fast, precise, and real-time manner and is able to cut existing distance boundaries. In this study, a wireless data monitoring system for the distribution of Covid-19 was created. This system uses a data parsing method that utilizes the Thingspeak application, to process data using the Arduino IDE and utilizing the ESP8266 as a wireless data transmission medium. The processed data is then displayed on an OLED layer.